A Fibi S’ólóore- A Study of Olúṣẹ́gun Ọbásanjọ́ as a Fringe Yorùbá Elite - Oyesola Animashaun (Yoruba Studies Review)
Yorùbá minstrels highlight varied aspects of a person’s ancestral attributes. A constructed poem for a Yorùbá lineage, A fibi sú olóore, tí ó ta àna rẹ̀ lọ́fà, (an ingrate, who repays his in-laws by shooting at him) seem to fit Ọbásanjọ́ like a glove. The aim of the study is to identify the extent to which Ọbásanjọ́ has advanced himself by using the Yorùbá ethnic currency; and had advanced laws and policies which are detrimental to the Yorùbá national interest. The methodology adopted is qualitative and reliance is placed on Ọbásanjọ́’s own accounts, the undisputed renditions of his superiors, colleagues and associates. The work is examined through the prism of Machiavelli and elite theories.The study revealed that the mainstream Yorùbá elites continually fall prey to Ọbásanjọ́’s devices and concludes that the subject used the Yorùbá ethnic currency as a passport to glory in Nigerian public life at the detriment of his nation.